Ethanol Lock Treatment and Secondary Prophylaxis for Central Line-Associated Bloodstream Infection in Pediatric Hematology and Oncology: A Randomized, Double-Blind, Placebo-Controlled, Intervention Trial. (4th October 2017) - Wolf, Joshua; Connell, Tom; Allison, Kim J; Tang, Li; Richardson, Julie; Branum, Kristen; Borello, Eloise; Gaur, Aditya; Hakim, Hana; Su, Yin; Mechinaud, Francoise; Hayden, Randall; et al.
Abstract: Background: Central line-associated bloodstream infection (CLABSI) commonly affects children with cancer and hematological disorders, with significant attributable costs and morbidity. Treatment failure, comprising persistent infection, infection relapse or new infection, occurs in ~50% of cases. Adjunctive ethanol lock therapy (ELT) has been proposed to prevent failure, but has never been tested in a prospective controlled study. Methods: A prospective, dual-center, double-blind, block-randomized, placebo-controlled trial of ELT (70% ethanol in water) for CLABSI, given as treatment (2 hours per lumen per day) for 5 days, followed by secondary prophylaxis (2 hours per lumen up to 3 days per week) for 24 weeks, in children with oncologic or hematologic disorders (NCT01472965). Risk of treatment failure was compared between intervention and control groups according to proportional and cumulative incidence models, using intention-to-treat and per-protocol analyses. The study was discontinued at a pre-specified futility analysis. Results: Of 94 evaluable participants, 48 were randomized to ELT and 46 to placebo; groups were similar at baseline for all measured variables. Forty-one (43.6%) participants had treatment failure (11 early failure, 9 relapse, and 21 reinfection). There was no difference between patients receiving ELT or placebo for risk of treatment failure (43.8% vs. 43.5%; P = 0.9) or for cumulative incidence of treatment failure in intention to treat (Figure 1) and per-protocol analyses (Figure 2). Catheter occlusion was significantly more common in participants receiving ethanol (58.3% vs. 32.6%, P = 0.01) but other adverse events, including LFT elevations (14.6% vs. 26.1%) and infusion reactions (18.8% vs. 8.7%), were not significantly different between groups. Conclusion: Although observational studies suggested ELT might be effective for treatment of CLABSI in pediatric oncology, we found no benefit in treatment outcome and an increase in adverse effects. These results may not apply to patients receiving dialysis or with fungal CLABSI as these were not well-represented. Routine use of ELT for CLABSI in children with oncologic or hematologic disorders is not recommended. Disclosures: All authors: No reported disclosures.